Polymyalgia Rheumatica and Giant Cell Arteritis - Rovenský, Jozef; Leeb, Burkhard; Štvrtinová, Viera; Imrich, Richard (Springer International Publishing : Imprint: Springer, 2017)
This book, now in an extensively updated and expanded third edition, offers important insights into polymyalgia rheumatica (PMR) and giant cell arteritis (GCA), providing an overview of their pathophysiology, genetics, immunology, and endocrinological mechanisms but above all presenting the state of the art in diagnosis and treatment. Both PMR and GCA are diseases of advanced age. Early diagnosis and treatment can save one of the most precious senses - vision. In this book, the role of imaging techniques is thoroughly examined, with particular attention to ultrasonography and FDG PET. All aspects of management of both diseases are discussed, including the current use of glucocorticoids, the efficacy of modern biological treatment, such as infliximab, tocilizumab, and rituximab, and the available monitoring tools. Diagnostic criteria for PMR and GCA are outlined, with discussion of differential diagnosis. Among the other topics addressed are disease classification, the histopathology of GCA, the ACR criteria for temporal arteritis, the value of temporal artery biopsy in GCA, serum cytokine profiles, chronobiology, and sine syndromes. The reader will find that the book aids in achieving early diagnosis and providing faster and more effective disease management. General readers with an interest in rheumatology, internal medicine, oftalmology and gerontology will find this book particularly valuable.
Keywords: Medicine.; Geriatrics.; Rheumatology.; elektronické knihy; electronic books